2021
DOI: 10.3390/curroncol28030179
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Testis Antigen, NOL4, Is an Immunogenic Antigen Specifically Expressed in Small-Cell Lung Cancer

Abstract: To identify cancer/testis (CT) antigens and immunogenic proteins, immunoscreening of testicular and small-cell lung cancer cell line NCI-H889 cDNA libraries was performed using serum obtained from a small-cell lung cancer (SCLC) patient. We obtained 113 positive cDNA clones comprised of 74 different genes, designated KP-SCLC-1 through KP-SCLC-74. Of these genes, 59 genes were found to be related to cancers by EMBASE analysis. Three of these antigens, including KP-SCLC-29 (NOL4), KP-SCLC-59 (CCDC83), and KP-SCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Motylewska et al 49 examined the mRNA and protein levels of NEK2 in 22 cases of SCLC and found that elevated levels of NEK2 expression could be observed in patients with SCLC. Kim et al 50 revealed that NOL4 was expressed highly in SCLC and weakly or undetectably in non-SCLC, suggesting that NOL4 could act as a potential tumor antigen in SCLC. Güre et al 51 detected the expression of ZIC2 mRNA in 11 SCLC cell lines and normal tissues with PCR, and the result showed that ZIC2 was detected in 9 out of 11 SCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Motylewska et al 49 examined the mRNA and protein levels of NEK2 in 22 cases of SCLC and found that elevated levels of NEK2 expression could be observed in patients with SCLC. Kim et al 50 revealed that NOL4 was expressed highly in SCLC and weakly or undetectably in non-SCLC, suggesting that NOL4 could act as a potential tumor antigen in SCLC. Güre et al 51 detected the expression of ZIC2 mRNA in 11 SCLC cell lines and normal tissues with PCR, and the result showed that ZIC2 was detected in 9 out of 11 SCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…CTA can be used as an immunotherapy target mediated by cytotoxicity T lymphocyte [23]. Some CTAs were identified to have immunogenicity, indicating the possibility of tumor immunotherapy targets [24][25][26]. In previous studies, compared with NY-ESO-1 (10.5%), which has been used in clinical immunotherapy, KK-LC-1 (32.6%) has a higher expression level in NSCLC [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigations are necessitated to fully explore the effects of these genes on bone biology. The protein encoded by Nol4 is associated with RNA binding and has been identified as a cancer/testis antigen in humans, recently presented as a candidate target in small cell lung cancer ( Kim et al, 2021 ). However, the role of Nol4 in bone-related pathologies remains to be fully explored.…”
Section: Discussionmentioning
confidence: 99%